2011
DOI: 10.1111/j.1439-037x.2011.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of Wheat by Seed Priming Under Saline Conditions

Abstract: Salinity is one of a major threat in harvesting good wheat stand on sustained basis. In this study, potential of seed priming techniques to improve the performance of wheat varieties (SARC‐1 and MH‐97) in a saline field was tested. For priming, wheat seeds were soaked in aerated solution of ascorbate (50 mg l−1; ascorbate priming), salicylic acid (50 mg l−1; salicylicate priming), kinetin (50 mg l−1; kinetin priming) and CaCl2 (50 mg l−1; osmopriming) for 12 h. For comparison, seeds were also soaked in simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
90
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(103 citation statements)
references
References 28 publications
11
90
0
2
Order By: Relevance
“…Two treatments (+Mo and −Mo) were applied to seeds of both varieties. Half of the seeds from each genotype were soaked in a solution containing 1% molybdate (NH 4 ) 6Mo7O 24 ·4H 2 O] (0.008 M) for 8 h at 20°C (Wang et al 1999;Jafar et al 2012), and the other half were soaked in distilled water for the same period (hydro priming) and then air dried until they reached their original moisture content (14%) (Ahmadi et al 2007). Seeds were then sown in trays in a growth cabinet (Snijder scientific) in order to obtain seedlings at the same physiological age.…”
Section: Seed Treatment With Mo and Plant Materialsmentioning
confidence: 99%
“…Two treatments (+Mo and −Mo) were applied to seeds of both varieties. Half of the seeds from each genotype were soaked in a solution containing 1% molybdate (NH 4 ) 6Mo7O 24 ·4H 2 O] (0.008 M) for 8 h at 20°C (Wang et al 1999;Jafar et al 2012), and the other half were soaked in distilled water for the same period (hydro priming) and then air dried until they reached their original moisture content (14%) (Ahmadi et al 2007). Seeds were then sown in trays in a growth cabinet (Snijder scientific) in order to obtain seedlings at the same physiological age.…”
Section: Seed Treatment With Mo and Plant Materialsmentioning
confidence: 99%
“…The ability of plants to survive and produce harvestable yields under salt stress is called salt resistance. Salt resistance is a complex phenomenon, and plants manifest a variety of adaptations at subcellular, cellular, and organ levels such as stomatal regulation, ion homeostasis, hormonal balance, activation of the antioxidant defense system, osmotic adjustment, and maintenance of tissue water status to grow successfully under salinity (Neubert et al 2005;de Azevedo Neto et al 2006;Hichem et al 2009;Schubert et al 2009;Kaya et al 2010;Jafar et al 2012). An integrated approach encompassing conventional breeding together with marker-assisted selection, biotechnology, exogenous use of growth regulators/ osmoprotectants, and nutrient management may be needed for successful maize cultivation on salt-affected soils (Eker et al 2006;Gunes et al 2007;Janmohammadi et al 2008;Kaya et al 2010;Li et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Harris (1996) demonstrated that simply soaking seeds in plain water before sowing could increase the speed and homogeneity of germination and emergence, leading to better crop stands, and stimulated seedlings to grow much more vigorously. Hydro priming, a simple hydration technique to a point of pregermination metabolisms without actual germination (Farooq et al, 2009b), is one of the most pragmatic, simple, economic and short-term approaches to combat the effects of drought (Kaya et al, 2006) and other abiotic stresses (Jafar et al, 2012) on seedling emergence and crop establishment. Hydro primed seeds usually have early, higher and synchronized germination owing to reduction in the lag time of imbibitions otherwise required much time (Brocklehurst and Dearman 2008) and build-up of germination enhancing metabolites (Farooq et al, 2006).…”
Section: Introductionmentioning
confidence: 99%